The New Moses and the Wisdom of God: A Convergence of Themes in Matthew 11:25–30 - Sharbaugh, Patricia (Horizons, 2013)
This article focuses on the confluence of Wisdom and Mosaic themes in Matthew 11:25-30, asserting that the convergence of these two themes points to an association between wisdom traditions and salvation history that is often overlooked. The two traditions evolved as Israel, trying to live life in obedience to Torah, encountered sin, suffering, trial, mystery, and an often turbulent history. As Israel encountered new and often painful life experiences, they remembered and appealed to tensive metaphors and traditions in order to understand the new experience and to provide stability in the midst of changing history. Recognizing that God's revelation in Jesus is a mystery both transcending and occurring within human experience, Matthew uses traditional tensive metaphors in order to emphasize that while the revelation of God's salvation in Jesus Christ is new, it is grounded in and continuous with salvation history. At the same time, this mystery transcends former expression. By describing Jesus as both a new Moses and personified Wisdom, Matthew imaginatively combines the symbolic worlds evoked by these two metaphors. The convergence of these symbolic worlds assures that Christological reflection moves beyond the familiar and is open to the mystery of God's revelation in Christ.